(untitled) (Biological Sciences - PJSIR, 1997)
The heterogeneity of adenylate cyclase (AC) of Bordetella pertussis reported in the literature has been revealed by SDS-PAGE and immunoblotting. This signifies that AC might be susceptible to endogenous proteases. The multiplicity of the bands appeared in SDS-PAGE and immunoblotting were found to be reduced when a protease inhibitor, phenyl methyl sulphonyl flouride (PM SF) was used during AC preparation. This study indicates that AC does not exist physiologically as multiple peptides.